Development of Questionnaire on Students' Perceptions of STEM and Problem-solving (SPSP): a Rasch Modelling Approach - Eis Nurzakiyah; Ghina Aghnia Nur Assyifaa; Ida Kaniawati; Irma Rahma Suwarma (Radiasi : Jurnal Berkala Pendidikan Fisika, 2021)
This study aims to prove empirically the validity and reliability of Questionnaire on Students' Perceptions of STEM and Problem-solving (SPSP) in learning physics using Rasch model. The questionnaire was disseminated to 59 (N=59) students class XI MIPA in one of Senior High School in Kuningan Regency. Development of SPSP Questionnaire using procedure of product development model 4-D. The stages that will be used consists of four stages, namely: a) define, b) design, c) development, and disseminate. The data obtained were analyzed by means of the Rasch Model. Based on the result of the study, it shows that the SPSP questionnaire had high reliability that 0.90. So, it can be concluded that SPSP questionnaire is reliable and acceptable. While the item validity analysis shows that there are 8 valid items and 1 item does not match the MNSQ benchmark. Outfit value lies between 0.5 <MNSQ <1.5 and also does not meet the ZSTD Outfit criteria (-2.0 <ZSTD <2, 0). Meanwhile, the students' responses indicate that learning in school has not supported STEM activities and problem solving. So it is necessary to develop learning in schools that can support STEM activities and students' problem solving abilities